Application of Physiologically Based Absorption Modeling for Amphetamine Salts Drug Products in Generic Drug Evaluation. Issue 9 (13th May 2015) - Babiskin, Andrew H.; Zhang, Xinyuan; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; Tamai, Ikumi; Vig, Balvinder; Yu, Lawrence X.
<x xml:space="preserve">Abstract</x> Amphetamine (AMP) salts‐based extended‐release (ER) drug products are widely used for the treatment of attention deficit hyperactivity disorder. We developed physiologically based absorption models for mixed AMP salts ER capsules and dextroamphetamine sulfate ER capsules to address specific questions raised during generic drug postmarketing surveillance and bioequivalence (BE) guidance development. The models were verified against several data sets. Virtual BE simulations were conducted to assess BE in various populations other than normal healthy subjects where BE studies are generally conducted for approval. The models were also used to predict pharmacokinetics (PK) for hypothetical formulations having dissolution profiles falling within specification after the development of in vitro–in vivo relation. Finally, we demonstrated how to use the models to test sensitivity of PK metrics to the changes in formulation variables. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3170–3182, 2015